Constructing an uncertainty budget for voltage RMS measurement with a sampling voltmeter. (24th January 2018) - Krajewski, Mariusz
Abstract: This paper presents a way of constructing an uncertainty budget for root mean square (RMS) voltage measurement with an integrating sampling voltmeter and a discreet Fourier transform (DFT) algorithm. The construction of an uncertainty budget based on the Monte Carlo method is proposed. Such a budget makes it possible to analyse metrological properties of RMS measurement, especially in cases difficult to realize by the classical method of uncertainty determination. An application of the proposed research method is illustrated by voltage RMS measurement with a high-accuracy HP3458A sampling voltmeter. Selected simulation results have been experimentally verified.